Legal Protection Model for Indonesian Migrant Workers - Widyawati, Anis (Universitas Negeri Semarang, 2018)
The emergence of several large cases of migrant workers in Malaysia and Singapore as well as in several Middle Eastern countries, especially Saudi Arabia, made all the nation's components flinch. Many people argue that the problem occurs because of the low level of education of migrant workers. There are also those who say that this problem occurs because employers of Indonesian labor services companies (Pengerah Jasa Penyalur Tenaga Kerja Indonesia, PJTKI, now called Perusahaan Penyalur Tenaga Kerja Indonesia Swasta, PPTKIS) are not nationally minded and only pursue profit (profit-oriented). There were also those who argued that the cases of migrant workers occurred due to the inactivity of regulative and punitive functions of the Government of the Republic of Indonesia. Based on the background above, the problem can be formulated is how the urgency of legal protection for Indonesian migrant workers abroad and how the legal protection model for Indonesian migrant workers abroad. Research carried out at BP3TKI and the Semarang Manpower and Transmigration Office underlined that legal protection for Indonesian migrant workers abroad is very important. The urgency in legal protection due to fulfillment of the rights of victims who work legally abroad but also cannot be fully implemented properly, due to differences in legal systems with migrant workers recipient countries that do not necessarily want to protect the rights of migrant workers who experience treatment not please from their own citizens. The migrant workers who work illegally the government has not been able to fully protect the rights of victims who have experienced criminal acts. The legal protection model for migrant workers currently emphasizes the fulfillment of victims’ rights who work legally abroad, such as obtaining legal assistance from a local lawyer appointed by the ambassador of the Republic of Indonesia in the country receiving the migrant workers, mentoring by psychologists and clergy, bringing the families of victims, compensation, and insurance claims. And at the same time, for migrant workers who work illegally the government has not been able to fully protect the rights of the victims.